Parameter Analysis of COD and BOD Liquid Waste at Sidoarjo Steel Company 2022 - Suryaningrum, Lina; Adriyani, Retno (Jurnal EduHealth, 2023)
Waste is material or substance originating from a production process, both industrial and domestic. Steel companies in Sidoarjo monitor their domestic waste referring to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia number P.68/Menlhk/Setjen/Kum.1/8/2016 concerning Domestic Wastewater Quality Standards. This study aims to analyze the COD and BOD parameters resulting from the processing of domestic waste from a steel company in Sidoarjo. This research is a non-reactive research, presenting information with secondary data sources from monitoring the quality of domestic wastewater and presented in a narrative descriptive manner. Sampling of wastewater at primary treatment outlets at 5 points, every month in 2022. COD and BOD analysis is carried out in the laboratory with procedures according to SNI. The results of monitoring the COD parameter tended to fluctuate and did not exceed the established quality standards, the same for the BOD parameter. It was concluded that the quality of the steel company's domestic waste for COD and BOD parameters met the applicable environmental quality standards